Construction on body image and levels of self-esteem and body satisfaction of middle-aged Filipino women in Iloilo Central Elementary School. - Hibionada, Dominique Ishmaielle S. (2018.)
The study was conducted to describe the body image of middle-aged Filipino women, as well as to determine their levels of self-esteem and body satisfaction, and to describe the possible consequences of body satisfaction or dissatisfaction. Seventeen (17) teachers from Iloilo Central Elementary School served as participants for the study. They were working mothers whose ages are from 40 to 54. Four instruments were utilized namely: Sociocultural Attitudes Towards Appearnce Questionnaire-3 (Thompson, van den Berg, Roehrig, Guarda, & Heinberg, 2003), Rosenberg Self-Esteem Scale (1965), Body Satisfaction Scale (Slade, Dewey, Newton, Brodie, & Kiemle, 1990), and an interview guide questionnaire constructed by the researchers. Results show that middle-aged women from the school have a positive body image. They also have a high level of self-esteem and body satisfaction. Faith to God, perceived healthiness of the body, body sizes, weight, and dietary practices are the reasons of their body satisfaction.
Research Project (Undergraduate, Bachelor of Arts (Psychology and Sociology) College of Arts and Sciences, Univetsity of the Philippines Visayas, Miagao, Iloilo.
Keywords: Women -- Middle Aged Filipino -- Iloilo Central Elementary School; Women -- Middle Aged Filipino